High temperature flow behavior and deformation mechanism of Nb-22.5Cr-2.5Mo alloy - Liping Deng; Shiqiang Lu; Xuan Xiao; Jiancong JiangFeng (Journal of Materials Research and Technology, 2022)
The high temperature compression is performed by isothermal compression tests using Gleeble 3500 thermo-mechanical simulator at a constant strain rate for the hot-pressed Nb-22.5Cr-2.5Mo alloy. The deformation temperature ranges from 800 to 1200 °C and the strain rate ranges from 0.001 to 0.1 s−1. The high temperature flow behavior and deformation mechanism of the alloy are investigated based on the compression test data and TEM observation of the deformed microstructure. The results show that the ductile–brittle transition temperature of the alloy is about 800 °C, and the flow stress is sensitive to the deformation temperature and strain rate, in which the plastic deformation ability increases obviously with the increase of deformation temperature and the decrease of strain rate. Besides, the hyperbolic sine Arrhenius model with stress exponent of 3.131 and apparent activation energy of 402 kJ/mol is established for the peak flow stress. The value of apparent activation energy is higher than that of Nb metal (246 kJ/mol), which implies the existence of Laves phase NbCr2 makes the deformation of the alloy more difficult. Moreover, it is found that the deformation mechanisms in the Nbss matrix are mainly DRV controlled by the glide and climb of the dislocations and DRX formed by bulging nucleation mechanism, while the deformation mechanisms in the Laves phase NbCr2 particles are mainly twinning and synchroshear of the Shockley partial dislocation.